2004
DOI: 10.1007/s00467-003-1395-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic uremic syndrome induced by lipopolysaccharide and Shiga-like toxin

Abstract: Induction of experimental hemolytic uremic syndrome (HUS) by simply administering Shiga-like toxin (Stx) to rodents has not yet been successful. Attention has been paid to the role of lipopolysaccharide (LPS) in the pathogenesis of HUS. In this study, we showed successful induction of an experimental HUS in LPS responder mice by administering Stx together with LPS. Intraperitoneal administration of 200 ng of Stx 2 for 2 days, followed by 250 microg of LPS on the 2nd day of Stx administration, caused a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 14 publications
8
61
0
Order By: Relevance
“…A few studies showed that there were consistent vascular or glomerular lesions (12,16,48), and the descriptions of these lesions varied between studies, confirming our findings that glomerular disease is present but mild in EHEC-infected mice. Several studies that used an injection model, in which Stx or Stx in combination with lipopolysaccharide was injected parenterally into mice, described glomerular lesions (11,13,15,20,45), supporting our finding that virulent EHEC is capable of inducing glomerular disease in mice.…”
Section: %)supporting
confidence: 89%
“…A few studies showed that there were consistent vascular or glomerular lesions (12,16,48), and the descriptions of these lesions varied between studies, confirming our findings that glomerular disease is present but mild in EHEC-infected mice. Several studies that used an injection model, in which Stx or Stx in combination with lipopolysaccharide was injected parenterally into mice, described glomerular lesions (11,13,15,20,45), supporting our finding that virulent EHEC is capable of inducing glomerular disease in mice.…”
Section: %)supporting
confidence: 89%
“…In a baboon model of HUS, LPS increased the toxicity of Stx (58). Consistently, both Stx2 and LPS were required to elicit a HUS-like response in mice (16,36,42). Our experiments document that in mice treated with Stx2/LPS that developed thrombocytopenia and renal failure, enhanced P-selectin expression on glomerular endothelial cells preceded C3 deposits.…”
Section: Discussionsupporting
confidence: 71%
“…The dosing protocol was based on previous studies (16,36). Mice were sacrificed at 3, 6, 24, or 48 h after injection.…”
Section: Experimental Model Of Husmentioning
confidence: 99%
“…Therefore, the effects previously ascribed to Stx2 in murine podocytes may be due to a small contaminating dose of LPS. Furthermore, the murine glomerular endothelial cells displayed similar responses to LPS and insensitivity to Stx2, suggesting that murine models reporting glomerular damage are likely due to LPS or indirect effects of Stx2; only those models that use live STEC or inject mice with Shiga toxin plus LPS observe glomerular defects (13,28,33,59,63). Although the Stx2-induced HUS mouse model lacks glomerular damage, we believe this difference from human disease does not preclude the utility of this system.…”
Section: Vol 77 2009mentioning
confidence: 95%
“…Although multiple groups have been unable to locate the Shiga toxin receptor Gb 3 in glomeruli in murine renal sections (19,53), one group has reported that murine glomerular podocytes possess Gb 3 and respond to Stx2 in vitro (40), and another group has reported that renal tubular capillaries express the Gb 3 receptor (46). Furthermore, murine glomerular abnormalities, including platelet and fibrin deposition, occur in some murine HUS models (28,30,33,46,59,63). We demonstrate here that murine glomerular endothelial cells and podocytes are unresponsive to Stx2 because they do not produce the glycosphingolipid receptor Gb 3 in vitro or in vivo.…”
mentioning
confidence: 99%